Rare Variants in PLD3 Do Not Affect Risk for Early-Onset Alzheimer Disease in a European Consortium Cohort - Cacace, Rita; Van den Bossche, Tobi; Engelborghs, Sebastiaan; Geerts, Nathalie; Laureys, Annelies; Dillen, Lubina; Graff, Caroline; Thonberg, Håkan; Chiang, Huei-Hsin; Pastor, Pau; Ortega-Cubero, Sara; Pastor, Maria A; et al. (Human mutation, 2015)
Rare variants in the phospholipase D3 gene (PLD3) were associated with increased risk for late-onset Alzheimer disease (LOAD). We identified a missense mutation in PLD3 in whole-genome sequence data of a patient with autopsy confirmed Alzheimer disease (AD) and onset age of 50 years. Subsequently, we sequenced PLD3 in a Belgian early-onset Alzheimer disease (EOAD) patient (N = 261) and control (N = 319) cohort, as well as in European EOAD patients (N = 946) and control individuals (N = 1,209) ascertained in different European countries. Overall, we identified 22 rare variants with a minor allele frequency <1%, 20 missense and two splicing mutations. Burden analysis did not provide significant evidence for an enrichment of rare PLD3 variants in EOAD patients in any of the patient/control cohorts. Also, meta-analysis of the PLD3 data, including a published dataset of a German EOAD cohort, was not significant (P = 0.43; OR = 1.53, 95% CI 0.60-3.31). Consequently, our data do not support a role for PLD3 rare variants in the genetic etiology of EOAD in European EOAD patients. Our data corroborate the negative replication data obtained in LOAD studies and therefore a genetic role of PLD3 in AD remains to be demonstrated.
Keywords: Odds Ratio; věk při počátku nemoci; Age of Onset; lidé; Middle Aged; Adult; Case-Control Studies; odds ratio; Phospholipase D; Evropa; Alzheimerova nemoc; Humans; genetická variace; Risk; vysoce účinné nukleotidové sekvenování; studie případů a kontrol; High-Throughput Nucleotide Sequencing; lidé středního věku; Meta-Analysis as Topic; kohortové studie; Alternative Splicing; Cohort Studies; fosfolipasa D; alternativní sestřih; riziko; genetická predispozice k nemoci; Alzheimer Disease; Exome; Alleles; Aged; alely; Europe; exom; Genetic Predisposition to Disease; dospělí; senioři; Genetic Variation; metaanalýza jako téma